A chiral smectic phase induced by an alternating external field. Issue 13 (16th March 2022) - Chen, Zi-Qin; Sun, Yu-Wei; Zhu, You-Liang; Li, Zhan-Wei; Sun, Zhao-Yan
Abstract : Chiral helical structures are obtained for ellipsoids under alternating external fields. Abstract : Using simple achiral building blocks modulated by an external field to achieve chiral liquid crystal phases remains a challenge. In this study, a chiral helix liquid crystal phase is obtained for a simple Gay–Berne ellipsoid model under an alternating external field by using molecular dynamics simulations. Our results show that the chiral helix liquid crystal phase can be observed in a wide range of external field strengths when the oscillation period is smaller than the rotational characteristic diffusion timescale of ellipsoids. In addition, we find that the pitch and tilt angle of the helix structure can also be adjusted by changing the strength and oscillation period of the applied alternating external field. This may provide a feasible route for the regulation of chiral liquid crystal phases by an alternating external field.